6.2k views
4 votes
How do you solve g= y-c+x for x

User Vamin
by
4.9k points

2 Answers

4 votes

You would subtract y and add c to both sides and you’ll get x=g-y+c

User Manoj Salvi
by
5.8k points
2 votes
To solve for x just isolate x by moving the other variables so....:
First add c to both sides
g+c= y+x
Subtract y from both sides
g+c-y= x
That should be your final answer (we cannot come up with an actual digit for x because there are no numbers in this equation we simply can make an equation for x)
User Talie
by
5.6k points